Role of perceived spousal social support in medication adherence among hypertensive patients attending family medicine clinic in federal teaching hospital, ido-ekiti, Nigeria - Ekundayo OO; Elegbede OT; Gabriel-Alayode OE; Agboola SM; Shabi OM; Bello IS; Omosanya OE; Ajetunmobi OA; Fashola AM (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: There abound many strategies to control hypertension, however, many patients still have difficulty adhering to medications and this results to poor Blood Pressure (BP) control. And because the condition requires life - long treatment, many patients need additional effort from their spouses. The spouse shares intimacy with patient and is the chief source of social support that provides financial assistance, reminds and encourages medication use, shows concern and interest by discussing issues related to the disease. Therefore, exploring the role of perceived spousal social support in medication adherence will help the physician and other stakeholders harness the gains of this association to achieving BP control, prevent complications and death. Objectives: To determine the relationship between Perceived Spousal Social Support (PSSS) and Medication Adherence (MA) among hypertensive patients attending Family Medicine Clinic in Federal Teaching Hospital, Ido-Ekiti, Nigeria. Materials and methods: It was a hospital - based cross - sectional analytical study carried out among 298 hypertensive patients aged between 18 and 65 years between June and August 2016 at the Family Medicine Clinic of the Federal Teaching Hospital, Ido Ekiti. Data collection was done using pre-tested, semi-structured questionnaire on sociodemographic characteristics, blood pressure measurement, Morisky Medication Adherence Scale (MMAS-8) for medication adherence and a 4-point Likert Social Support questionnaire for compliance to measure the perceived spousal social support. Data was analysed using SPSS IBM version 17.0. Results: The mean age of respondents was 56.0 ± 8.5 years. Overall, there was a statistically significant relationship between PSSS and MA (χ2 = 17.93, p < 0.001). Gender and PSSS were found to be independent predictors of MA. Conclusion: Spousal social support impacts positively on medication adherence, therefore exploring this social resource will improve MA and the management outcomes of hypertension.